Um estudo sobre as possíveis contribuições da gestão baseada em evidências para as gestões da evasão e da permanência de estudantes, no IFG Câmpus Inhumas (2015-2019) - Lima, Rafael Soares de (2022)
Access, followed by the retention and success of students in higher education, can be understood as an opportunity to be equitably distributed, in accordance with Rawlsian principles of justice. In this sense, it is important to reflect on higher education institutions as implementers of public policies. Thus, this dissertation aimed to investigate the possible contributions of Evidence-Based Management (EBM) for the management of student dropout, retention and success, at IFG Câmpus Inhumas, in view of the performance of the Student Retention and Success Committee, between 2015 and 2019. Methodologically, the study was based on exploratory and bibliographic research, with document analysis and data collection through a questionnaire and interview. Similarities were found between the institutional challenges of dropout, retention na success management, and the stages of EBM. The agreement of the members of the Committee in relation to these institutional challenges, the role of the Committee and the principles of EBM was also observed. However, difficulties were identified in the organization of the Committee's activities, such as frequency of meetings, division of tasks, fulfillment of all attributions and interaction with other sectors of the Campus. In view of these findings, a proposal for the organization of the Committee's activities was elaborated.